The Ability of Linen Housekeeping Treatment Practice for Students’ Field Practice Readiness in SMK 45 Lembang - Aisah, Diana Rahmi; Rohaeni, Neni; Ningsih, Mirna Purnama (FamilyEdu: Jurnal Pendidikan Kesejahteraan Keluarga, 2019)
The background of this research is the importance of students’ ability in linen housekeeping treatment as field practice readiness in accordance to hotel’s standard operating procedure. The aim of this research is to gain the data of linen housekeeping treatment practice as field practice readiness in SMK 45 Lembang. The method used in this research is descriptive method. The instrument uses performance criteria from Guttman Scale. The sample used in this research is the total sample of 39 students. The result of this research is that the ability of linen housekeeping treatment practice in accordance to hotel’s standard operating procedure encompass three phases done by students, which are preparation, execution, and result. In preparation phase, students are able to maintain their personal hygene and their work uniforms. In execution phase, students are able to do linen delivery, reception, and storage. In result phase, students are able to tidy out linen. All of the students are able to tend the linen well in accordance to hotel’s standard operating procedure, but a small number of the students are unable to do so as their field practice readiness. The recommendation for the teachers is to keep giving linen-related knowledge to the students in order to prepare them for field practice.